1998
DOI: 10.1046/j.1365-3083.1998.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Responses of Peripheral Blood Leucocytes of Sheep Infected with Trypanosoma evansi

Abstract: The effects of Trypanosoma evansi on the proliferative responses of ovine peripheral blood leucocytes (PBL) were examined in in vitro cell culture systems. Sheep were vaccinated against pneumonic pasteurellosis with a monovalent Pasteurella haemolytica vaccine and then infected with T. evansi TREU 2143. From 1 week post-infection (p.i.), the PBL were separated and stimulated in cultures with either Concanavalin A (Con A), bacterial lipopolysaccharide (LPS), pasteurella antigen (P.ag), or homologous trypanosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Group A appeared to have recovered from the immunosuppressive effect by day 28 post trypanocidal treatment with quinapyramine prosalt (day 56 PPV) as observed by antibody titres which were similar to that in group C. No significant difference in antibody titres was observed between these two groups. Similar to the present study, trypanocidal therapy of T. evansi-infected sheep was able to restore the proliferative activity of ovine peripheral blood leucocytes to mitogens (Onah et al 1998c). However, these workers have shown that, though the specific responses to homologous antigen were restored after trypanocidal treatment, yet, response to heterologous Pasteurella antigen were lower in infected and treated sheep compared with uninfected healthy controls.…”
Section: Hs-specific Antibody Responsessupporting
confidence: 88%
See 1 more Smart Citation
“…Group A appeared to have recovered from the immunosuppressive effect by day 28 post trypanocidal treatment with quinapyramine prosalt (day 56 PPV) as observed by antibody titres which were similar to that in group C. No significant difference in antibody titres was observed between these two groups. Similar to the present study, trypanocidal therapy of T. evansi-infected sheep was able to restore the proliferative activity of ovine peripheral blood leucocytes to mitogens (Onah et al 1998c). However, these workers have shown that, though the specific responses to homologous antigen were restored after trypanocidal treatment, yet, response to heterologous Pasteurella antigen were lower in infected and treated sheep compared with uninfected healthy controls.…”
Section: Hs-specific Antibody Responsessupporting
confidence: 88%
“…Onah et al (1997) showed that T. evansi infection inhibits blast cell output and plays a role in induction of immunosuppression. They considered trypanosome-induced immunosuppression to be a serious practical impediment to vaccine-based disease control programme in the regions where trypanosomes are endemic (Onah et al 1998c;Holland et al 2001).…”
Section: Hs-specific Antibody Responsesmentioning
confidence: 99%
“…In water buffaloes, T. evansi infection induced a significant decrease in haemoglobin concentration, packed cell volume (PCV) and red blood cell count, kidney function (creatinine and urea), and liver alkaline phosphatase, whereas total the leucocytic count, lymphocyte, and monocyte populations increased, as well as liver functions (lactate dehydrogenase enzyme (LDH) activity, globulin, total bilirubin, and indirect bilirubin), showing a direct link between immune and metabolic disorders [183188]. In experimentally infected sheep, dissection of the immune components involved in T. evansi -induced immunosuppression highlighted that macrophages but not CD8(+) T cells were mainly responsible for suppression [189].…”
Section: Immunosuppressive Effectsmentioning
confidence: 99%
“…The same results were obtained when performing the experiment and analysis on lymphocyte phenotypes draining from a lymph node of a T. evansi -infected Pasteurella haemolytica -vaccinated sheep, allowing the authors to conclude that these abnormal changes in the kinetics of efferent lymphocyte phenotypes are likely to play a role in the genesis of the generalized immunosuppression seen in trypanosome-infected hosts [185]. Lastly, the proliferative responses of T. evansi -infected Pasteurella haemolytica -vaccinated ovine peripheral blood leucocytes (PBL) Concanavalin A (Con A), bacterial lipopolysaccharide (LPS), PASTEURELLA antigen (P.ag), or homologous trypanosome antigen (T.ag) were significantly suppressed by the infection, but fully restored by trypanocidal treatment for Con A, LPS and T.ag only, whereas for P.ag the responsiveness of cells from uninfected vaccinated sheep remained significantly higher than those of cells from infected sheep [183]. This strongly suggests that the immunosuppression induced by T. evansi may have an even more dramatic impact, because the treatment of trypanosome infection would have no impact on the loss of protection against common animal diseases.…”
Section: Immunosuppressive Effectsmentioning
confidence: 99%
“…B cell mitogens have been used in ovine PBL cultures to induce proliferative responses 12 , 13 , 14 , 15 . However, the potential for mitogens to drive cellular differentiation and antibody secretion has been ignored in this species although several studies report non‐specific Ig secretion in mitogen‐stimulated bovine PBL 9 , 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%